2018
DOI: 10.1002/jccs.201800002
|View full text |Cite
|
Sign up to set email alerts
|

In situ synthesis of C3N4/Bi2S3 composites with enhanced photocatalytic degradation performance under visible light irradiation

Abstract: Carbon nitride/bismuth sulfide (C3N4/Bi2S3) nanocomposites were prepared by a facile one‐step in situ calcination method using ammonium thiocyanate and bismuth chloride as reagents. The crystal structure, composition, and morphology of the nanocomposites were characterized by X‐ray diffraction (XRD), Fourier transform infrared (FT‐IR) spectroscopy, scanning electron microscopy (SEM), and transmission electron microscopy (TEM). The photocatalytic degradation of rhodamine B (RhB) was carried out to evaluate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…The final product includes g-C3N4/Bi2S3 and Bi. Yin et al [52] reported another method to prepare g-C3N4/Bi2S3 composite materials, through calcining the mixture of ammonium thiocyanate (NH4SCN) and bismuth chloride (BiCl3) at 550 °C in nitrogen atmosphere. In addition, the potential mechanisms for the enhanced photocatalytic activity of g-C3N4/Bi2S3 heterojunctions in these previous studies remained unclear or even contradictory.…”
Section: Introductionmentioning
confidence: 99%
“…The final product includes g-C3N4/Bi2S3 and Bi. Yin et al [52] reported another method to prepare g-C3N4/Bi2S3 composite materials, through calcining the mixture of ammonium thiocyanate (NH4SCN) and bismuth chloride (BiCl3) at 550 °C in nitrogen atmosphere. In addition, the potential mechanisms for the enhanced photocatalytic activity of g-C3N4/Bi2S3 heterojunctions in these previous studies remained unclear or even contradictory.…”
Section: Introductionmentioning
confidence: 99%
“…For evaluation of the solvent effect, the model reaction was investigated by applying various solvents (including EtOH, H 2 O, MeOH, CH 3 CN, toluene) and in solvent-free conditions (Table 1, entries [8][9][10][11][12].The results revealed that, in the presence of both types of protic and aprotic solvents, only a trace amount of product was obtained and the best result was achieved in the absence of solvent. In continuance, the influence of temperature was investigated (Table 1, entries [13][14][15][16][17]. Relying on the obtained results, as the temperature was conducted to 100 °C, the desired product was formed at a shorter reaction time and the yield increased to 87% (Table 1, entry 17).…”
Section: Resultsmentioning
confidence: 99%
“…Generally, g-C 3 N 4 substructure, based on aromatic C-N heterocycles and optimized van der Waals forces between its two-dimensional conjugated planes, can be prepared by polymerization of affordable nitrogen-containing materials like melamine, urea, cyanamide, thiourea, and dicyandiamide [6]. Reasonable physical and chemical property, unique electronic property, exclusive thermal and chemical resistance, and high specific surface area [7] make this material be applied in many scientific fields such as fuel cell [8], sensor [9], solar cell [10], metal-free catalyst [11], heterogeneous photocatalyst [12], energy storage [13], oxygen reduction reaction (ORR) [14], hydrogen evolution [15], photocatalytic degradation of pollutants [16,17], and oxidation [18]. The preparation of wellordered mesoporous g-C 3 N 4 leads to higher specific surface area, stronger adsorption capacity, and larger pore volume and increases active chemical sites, thereby enhancing the performance of g-C 3 N 4 as an efficient catalyst and catalyst support [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] In addition, Bi-based catalysts have been widely synthesized and studied. [15][16][17][18][19] However, studies on analyzing the correlations between structure variations of BiVO 4 and catalytic activities have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, bismuth vanadate oxides (BiVO 4 ) have been reported to show high catalytic performance among the mental oxide catalysts for the ammoxidation of methyl aromatics or heteroaromatics to nitriles 12–14 . In addition, Bi‐based catalysts have been widely synthesized and studied 15–19 . However, studies on analyzing the correlations between structure variations of BiVO 4 and catalytic activities have not been reported.…”
Section: Introductionmentioning
confidence: 99%